On uniform attractors for non-autonomous $p$-Laplacian equation with a dynamic boundary condition - Yang, Lu; Yang, Meihua; Wu, Jie (Topological Methods in Nonlinear Analysis, 2013)
In this paper, we consider the non-autonomous p-Laplacian equationwith a dynamic boundary condition. The existence and structure of a compact uniform attractor in $W^{1,p}(Ω)\timesW^{1-1/p,p}(Γ)$ are established for the case of time-dependentinternal force $h(t)$. While the nonlinearity $f$ and the boundarynonlinearity $g$ are dissipative for large values withoutrestriction on the growth order of the polynomial.